PENINGKATAN KEAMANAN IMIGRAN ASING OLEH PEMERINTAH INDONESIA DEMI CEGAH PENULARAN VIRUS COVID-19 - Martha Nindya Pratyaksa; Fatma Ulfatun Najicha (Borneo Law Review, 2022)
AbstractCurrently, the transmission of the COVID-19 pandemic virus in Indonesia is part of the 2019 coronavirus disease pandemic (COVID-19) that is ongoing worldwide. This disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which transmission can be through foreign immigrants. This affects the amendment of Government Regulation Number 31 of 2013 concerning Immigration to Government Regulation Number 48 of 2021 concerning Immigration in which there is the addition of new rules to Government Regulation Number 48 of 2021 concerning Immigration article 103 number 1 part (d) " declared free from infectious diseases that endanger public health "therefore this writing is to show the role of the government in Enhancing the Security of Foreign Immigrants by the Indonesian Government to Prevent Virus Transmission.Keywords: immigrants;government policies; the spread of the Covid -19 virus AbstrakSaat ini penularan virus pandemi COVID-19 di Indonesia merupakan bagian dari pandemi penyakit koronavirus 2019 (COVID-19) yang sedang berlangsung di seluruh dunia. Penyakit ini disebabkan oleh koronavirus sindrom pernapasan akut berat 2 (SARS-CoV-2) dimana penularannya bisa melalui para imigran asing.[1] Hal ini mempengaruhi perubahan  Peraturan Pemerintah Nomor 31 Tahun 2013 Tentang Keimigrasian menjadi  Peraturan Pemerintah Nomor 48 Tahun 2021 Tentang Keimigrasian dimana di dalamnya terdapat penambhan aturan baru pada Peraturan Pemerintah Nomor 48 Tahun 2021 Tentang Keimigrasian pasal  103 nomor 1 bagian  (d) “hasil pemeriksaan kesehatan yang menyatakan bebas dari penyakit menular yang membahayakan kesehatan umum”  maka dari itu dibuatnya tulisan ini ialah menunjukkan peran pemerintah dalam  Peningkatan Keamanan Imigran Asing Oleh Pemerintah Indonesia Demi Cegah Penularan Virus.Kata Kunci : imigran; kebijakan pemerintah ; penyebaran Virus covid -19[1] Diakses melalui https://id.wikipedia.org/wiki/Pandemi_COVID-19_di_Indonesia